Functional fitness in older women from southern brazil: normative scores and comparison with different countries - Gislaine Cristina Vagetti; Valter Cordeiro Barbosa Filho; Valdomiro de Oliveira; Oldemar Mazzardo; Natália Boneti Moreira; Antonio Carlos Gomes; Wagner de Campos (Universidade Federal de Santa Catarina, 2015)
Functional fitness loss during aging may compromise the quality of life and independence of older subjects. It is important to evaluate and diagnose the functional fitness of the elderly population. This study proposed normative functional fitness scores for a sample of elderly women from southern Brazil and compared values to their counterparts in the US, Extremadura (Spain), Taiwan (China) and Spain. The study sample consisted of 1,783 older women aged 60.0 to 84.9 years (mean 68.7 years; standard deviation 6.3 years) who performed the proposed motor tests of the "Senior Fitness Test" for functional fitness in older women. The percentile values specific to each age group were calculated based on the seven functional fitness components: body mass index, 6-minute walk, arm curl, 30-s chair stand, chair sit-and-reach, backscratch, and 8-feet up-and-go. The non-parametric binomial test compared the 50th percentile value of Brazilian older women with those from other countries. Older women´s performance in the functional capacity tests decreased across age groups. The mean BMI varied among age groups from 29.11 to 26.76 kg/m2, 6-minute walk from 572.94 to 486.95 m, arm curl from 17.51 to 15.11 repetitions, 30-schair stand from 15.62 to 14.30 repetitions, chair sit-and-reach from 1.01 to - 0.47 cm, back scratch from -4.92 to -10.52 cm and 8-feet up-and-go from 5.96 to 6.83 sec. Functional fitness scores among older women in different countries differed significantly. However, the direction and magnitude of differences were specific to the functional fitness component. Significant differences were observed in the normative scores, suggesting that the use of international normative scores in Brazilian older women may underestimate or overestimate potential functional limitations.